Interactive Game Development to Assist Cultural Heritage - László Márkus, Zsolt; Kaposi, Gábor; Veres, Miklós; Weisz, Zsolt; Szántó, György; Szkaliczki, Tibor; Paneva-Marinova, Desislava; Pavlov, Radoslav; Luchev, Detelin; Goynov, Maxim; Pavlova, Lilia (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2018)
Serious educational games provide a novel way to transfer knowledge on cultural heritage, which can especially attract young people by using interactive multimedia technology. The paper presents a new flexible tool for developing, managing and presenting games. This server-based solution can facilitate the game development by applying game templates, layout styles and question pools.It also supports the development of game packages for multiple languages and multiple platforms (Web and mobile). The games can easily be customised for various learning domains. Complex games can be composed from several socalled minigames (e.g. puzzle, multiple choice, memory game, crossword etc.) and the tool also supports the evaluation of the user answers and organising competitions. The games were applied to deepen knowledge on various topics related to our cultural heritage. The latest game development is represented by the serious educational game “The Thracians” running in a virtual 360º panorama environment, which presents the life, beliefs and traditions of the ancient tribes.
Keywords: Mobile Applications; Interactive Games; Serious Games; Game Development; Thracian Civilization